Perbandingan Platelet, Mpv Dan Pdw Pada Pasien Demam Dengue - Lumbantoruan, Gledys; Tania, Stefani (Syntax Literate, 2025)
Dengue fever is an infectious disease caused by the dengue virus with varying degrees of severity, ranging from Dengue Fever (DF), Dengue Hemorrhagic Fever (DHF), to Dengue Shock Syndrome (DSS). Hematological parameters such as platelet count, Mean Platelet Volume (MPV), and Platelet Distribution Width (PDW) are thought to play a role in assessing the severity of dengue. This study aims to compare platelet counts, MPV, and PDW values in dengue fever patients based on disease severity at Royal Prima Hospital Medan using an observational analytical design with a cross-sectional approach and secondary data from 47 patient medical records that met the inclusion criteria. Analysis was performed using the Shapiro-Wilk test and the Kruskal-Wallis test. The results showed a significant difference in platelet levels between the DF, DHF, and DSS groups (p=0.001), where platelet counts decreased at higher degrees of severity. In contrast, there was no significant difference in MPV (p=0.414) and PDW (p=0.499). Thus, only platelet levels were shown to differ significantly across dengue fever severity levels, while MPV and PDW did not play a significant role as indicators of disease severity.